A Rejoinder to: “Questioning the Appropriateness of Examining Guanxi in a Wasta Environment: Why Context Should be Front and Center in Informal Network Research – A Commentary on ‘De-Linking from Western Epistemologies: Using Guanxi-Type Relationships to Attract and Retain Hotel Guests in the Middle East’” - Shaalan, Ahmed; Eid, Riyad; Tourky, Marwa (Cambridge University Press (CUP), 2023)
This rejoinder responds to a commentary on our paper “De-Linking from Western Epistemologies: Using Guanxi-Type Relationships to Attract and Retain Hotel Guests in the Middle East”. We highlight the distinction we drew between guanxi itself and guanxi-type relationships to dispute the assertion that we imposed a Chinese concept onto a Middle Eastern context. Emphasising our own detailed knowledge of wasta, we explain why wasta was not a suitable umbrella term for the personal networks that operate in all 17 countries where our complex cross-cultural research took place, noting, however, that a discussion of this point would have enriched our study. We also refute a number of other specific criticisms of our methods and approach.